Hemispheric-Level Experience and Education Enables Solutions to Complex International Problems - Taylor, James (Hemisferio - Revista del Colegio Interamericano de Defensa, 2024)
Whether man-made or natural, complex problems facing the countries of the Western Hemisphere are challenging. They transcend national boundaries and affect countries differently. Bureaucracy appears to exacerbate them. Moreover, government-developed solutions are often ineffective and require a resource commitment level that burdens the taxpayer. Because a solution optimized for one country is not often as functional in another, effective solutions for complex international problems require the coordinated and synchronized efforts of all of the countries impacted by the problem. International problems require international solutions, and individuals with a hemispheric perspective to problem-solving are better able to develop those solutions. Service with, and education from, a hemispheric-level organization contributes to the cognitive and experiential development of the kinds of individuals who can then create solutions to complex international problems.